PERSPEKTIF CONNECTIVISME TERHADAP PENGGUNAAN MEDIA GAMIFIKASI DALAM PEMBELAJARAN DI SEKOLAH - Siti Nurjanah; Pina Indah Sayekti; Vitri Astuti; Bambang Sumardjoko; Endang Fauziati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the characteristics of Stephen Downes' Connectivism learning theory, the application of gamification media, and the Connectivism perspective on the use of gamification media in learning. This research is a descriptive qualitative study conducted at MI Muhammadiyah Karanganyar. Data collection techniques included observation, interviews, and documentation. The results of this study show that overall, gamification media applications such as Wordwall, Marbel Budaya Nusantara, and Quizizz have proven effective in enhancing engagement, motivation, collaboration, critical thinking skills, and appreciation for local culture. The integration of digital technology in learning through gamification can create a more engaging and productive learning environment for students. The use of gamification aligns with the principles of connectivism, where learning is considered a process that occurs within a network of social interactions and connections with various sources of information.